Efficiency Wages with Motivated Agents - Jesper Armouti-Hansen; Lea Cassar; Anna Deréky (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Many organizations nowadays combine profits with a social mission. This paper reveals a new hidden benefit of the mission: its role in facilitating the emergence of efficiency wages. We show that in a standard gift-exchange principals highly underestimate agents' reciprocity and, thereby, offer wages that are much lower than the profit-maximizing level. This bias has a high social cost: if principals had correct beliefs and thus offered the profit-maximizing wage, efficiency would increase by 86 percent. However, the presence of a social mission (in the form of a positive externality generated by the agent's effort), by increasing principals' trust, acts as a debiasing mechanism and, thereby, increases efficiency by 50 percent. These results contribute to our understanding of behavior in mission-oriented organizations, to the debate about the relevance of reciprocity in the workplace and open new questions about belief formation in prosocial contexts.
Keywords: D23; M52; 330; mission motivation; reciprocity; gift exchange; beliefs; efficiency wages